CRITICAL ANAESTHETIC INCIDENTS CAUSES AND ANALYSIS - Saleem Pervaiz Bajwa (Army Medical College Rawalpindi, 2019)
Objective: To improve the standard operating procedures (SOPs) for perioperative anesthesia management and reduction of complications where human error is involved.